Characteristics of pediatric injuries due to road traffic accidents and their effects on mortality - Akpinar, Guleser (Journal of Surgery and Medicine, 2021)
BackgroundAim: Road traffic accident (RTA)-related injuries may cause morbidity and mortality in childhood. We aimed to investigate these injuries in terms of affected body regions, time of the accident, gender, and age, determine the factors affecting mortality, and evaluate the casualties’ demographic features and discharge status. Methods: This retrospective cohort study included patients aged under 18 years who were victims of RTAs and presented to the emergency department of our tertiary university hospital between 01/01/2015 and 31/12/2019. Patients’ age, gender, time, and mechanism of the accident, affected body region, type of injury, and clinical outcomes were recorded and analyzed. Results: A total of 137 pediatric patients met the inclusion criteria, among which 95 (67.2%) were males, and 42 (32.8%) were females. Five of the six patients who died were males. RTAs most occurred in summer (45.3%), in August (17.5%) and on Saturdays (25.5%). Among the affected systems, extremity injuries ranked first (36.5%), and head traumas ranked second (30.7%). Conclusion: In our study, presentations with out of vehicle traffic accidents (OVTAs) (motorcycle, bicycle, agricultural vehicle, or pedestrian) were more common (75.1%). Pediatric RTAs caused many injuries, especially extremity traumas, which were more serious in children under 15 years of age. In these patients, intracranial hemorrhage, rib fractures, and liver lacerations were evaluated as more severe injuries. Because of the limited number of the cases, we could not investigate the effects of traffic accidents on child mortality.